2003
DOI: 10.1111/j.1875-595x.2003.tb00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Oro-facial injury and mouthguard usage by athletes in Nigeria

Abstract: Although the majority of the athletes claimed awareness of mouthguards, less than one-third used them. Over half of the athletes were not sure that mouthguards could reduce the prevalence and/or severity of oro-facial injuries. There is need to educate the athletes more concerning mouthguards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
1
12
0
3
Order By: Relevance
“…Previous studies showed enormous discrepancies in the awareness that mouthguard use prevents orofacial injuries. The reported rates of such awareness in other countries were 100% in Germany and Switzerland, 81.9% in Japan, 52.4% in Brazil, 27% in Israel, 82.8% in Nigeria, 44.1% in Turkey (8,(10)(11)(12)(13)(14). With the support of dentists and public health professionals, the risks of orofacial injury should be made known to athletes, parents, coaches, and school and college officials.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed enormous discrepancies in the awareness that mouthguard use prevents orofacial injuries. The reported rates of such awareness in other countries were 100% in Germany and Switzerland, 81.9% in Japan, 52.4% in Brazil, 27% in Israel, 82.8% in Nigeria, 44.1% in Turkey (8,(10)(11)(12)(13)(14). With the support of dentists and public health professionals, the risks of orofacial injury should be made known to athletes, parents, coaches, and school and college officials.…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde dental travma sebepleri ve oranları hakkında birçok bilgi bulunmaktadır [2][3][4][5][6]. En sık rastlanılan sebep düşme olmakla birlikte rapor edilen diğer sebepler Tablo 1' de sunulmaktadır.…”
Section: Tablo 1 Dental Travmaların Eti Yolojileriunclassified
“…Travmati k dental yaralanma ile dişe ve dişin destek dokularına gelen ani enerji transferinin sonucunda oluşan diş kırılmaları, yer değişikliği, dişin destek dokularıyla arasındaki bağlantı ların hasar görmesi, diş eti , komşu yumuşak dokularda ve kemikte zedelenmelerin meydana gelmesi biçiminde tanımlanmaktadır [1]. Literatürde dental travma sebepleri ve oranları hakkında birçok bilgi bulunmaktadır [2][3][4][5][6]. En sık rastlanılan sebep düşme olmakla birlikte rapor edilen diğer sebepler Tablo 1' de sunulmaktadır.…”
Section: Introductionunclassified
“…Although disadvantages such as impaired pronunciation and more difficulty breathing have been reported with MG use [1][2][3], proper MG design can overcome these problems [4,5]. Various reports have also been published that extol the usefulness of MGs in preventing trauma [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%